A case series of vaccine‐induced thrombotic thrombocytopenia in a London teaching hospital. Issue 4 (9th November 2021) - Watts, Isabella; Smith, David; Mounter, Sarah; Baker, Emma H.; Hitchings, Andrew W.; Gill, Dipender
Abstract : The ChAdOx1 nCoV‐19 vaccine has been associated with increased risk of thrombosis. Understanding of the management of these rare events is evolving, and currently recommended treatments include human normal immunoglobulin and nonheparin anticoagulation such as direct oral anticoagulants. Our report describes three consecutive patients presenting to a London teaching hospital with vaccine‐induced thrombotic thrombocytopenia (VITT), also referred to as vaccine‐induced prothrombotic immune thrombocytopenia. The patients ranged in age from 40 to 54 years and two had no known previous medical comorbidities. Two patients had cerebral venous sinus thrombosis and one had a deep vein thrombosis. Two were treated with anticoagulation, one with oral rivaroxaban and the other with an intravenous argotraban infusion that was later converted to oral apixaban. One patient received three doses of human normal immunoglobulin and 5 days of therapeutic plasma exchange. This case series may be used to improve understanding of the clinical course and management of VITT.